الاتصال الداخلي ودوره في تفعيل الأداء الوظيفي داخل المؤسسة الخدماتية - قدودة محمدالحبيب; نبق عمر; د/محمد تربح (جامعة عمار ثليجي الاغواط, 2023)
مخلص الدراسة: هدفت دراستنا بشكل عام الى التعرف على الاتصال الداخلي ودوره في تفعيل الأداء الوظيفي والى التعرف على الاتصال الداخلي وسائله المستخدمة في مؤسسة سونلغاز بالأغواط والكشف على مستوى الأداء الوظيفي بمؤسسة . وجرت دراستنا بمؤسسة سونلغاز بالأغواط، وانطلقت من إشكالية ما دور الاتصال الداخلي في تفعيل الأداء الوظيفي بمؤسسة سونلغاز بالأغواط ؟ وأجريت الدراسة على مجموعة من عمال مؤسسة سونلغاز بالأغواط البالغ عددهم 50 عاملا وعاملة ، وتم الاستعانة بالمنهج الوصفي واداة جمع البيانات الاستبيان وتم الوصول الى النتائج التالية: 1. مؤسسة سونلغاز بالأغواط تعتمد على عدة وسائل تساهم في تحسين فعاليات أداء عمالها ابرزها الزيارات الميدانية والبريد الالكتروني، كما ان عمال مؤسسة سونلغاز بالأغواط يرون ان عدم وجود وسائل اتصال حديثة قد يؤثر على أدائهم لمهامهم بشكل جيد. 2. مؤسسة سونلغاز نادرا ما تسمح لعمالهم بإبداء اراءهم وطرح اقتراحاتهم وفي حال سمحت بذلك تكون عبر الاجتماعات بأنواعها. 3. ان العملية الاتصالية داخل مؤسسة سونلغاز بالأغواط أحيانا ما تساعد العمال على أداء مهامهم . 4. عمال مؤسسة سونلغاز بالأغواط دائمو التواصل فيما بينهم حيث يرون ان نقص الاتصال بينهم يؤثر بشكل عام على الأداء المهني وسيرورة العمل. 5. العنصر النسوي من العمال داخل مؤسسة سونلغاز بالأغواط لا يؤثر على العملية الاتصالية داخل المؤسسة. الكلمات المفتاحية: الاتصال الداخلي - الدور - الأداء الوظيفي Study summary: Our study aimed, in general, to identify internal communication and its role in activating job performance, to identify internal communication and its means used in the Sonelgaz institution in Laghouat, and to detect the level of job performance in an institution. Our study was conducted at the Sonelgaz Foundation in Laghouat, and it started from the problem of what is the role of internal communication in activating job performance in the Sonelgaz Foundation in Laghouat? The study was conducted on a group of 50 workers of the Sonelgaz Corporation in Laghouat, and the descriptive approach and the questionnaire data collection tool were used, and the following results were reached: 1. The Sonelgaz Foundation in Laghouat relies on several means that contribute to improving the performance of its workers, most notably field visits and e-mail, and the workers of the Sonelgaz Foundation in Laghouat believe that the lack of modern means of communication may affect their performance of their tasks well. 2. The Sonelgaz Foundation rarely allows their workers to express their opinions and put forward their suggestions, and if they allow this, it is through meetings of all kinds. 3. The communication process within the Sonelgaz Corporation in Laghouat sometimes helps workers to perform their duties. 4. The workers of the Sonelgaz Corporation in Laghouat are always communicating with each other, as they see that the lack of communication between them generally affects the professional performance and the work process. 5. The female component of the workers within the Sonelgaz institution in Laghouat does not affect the communication process within the institution. Keywords: internal communication - role - job performance
(دراسة حالة مؤسسة سونلغاز